2021
DOI: 10.4103/idoj.idoj_613_20
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoscopy of Inflammatory Diseases in Skin of Color

Abstract: Dermatoscopy is a relevant in vivo diagnostic tool for inflammatory diseases of the skin that aids not only in diagnosis, but also in monitoring the response to treatment. The inflammatory diseases show dermoscopic patterns involving the vessels, scales, follicles, background hue, and special clues. This review aims to provide an overview on the use of dermoscopy in inflammatory dermatoses based on the available literature and the deviation from it in the skin of color (SOC) as there is paucity of literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
0
12
0
8
Order By: Relevance
“…This concordance is probably because of similarity in patient characteristics in terms of darker skin phenotypes. A review also reported that blood vessels are not visualized in pityriasis rosea lesions in dark skin 5 . This is discordant to studies done in Greece, Turkey, and India where they reported different blood vessel types and patterns since they involved mostly patients of types IV and lighter Fitzpatrick skin types 3,4,9 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This concordance is probably because of similarity in patient characteristics in terms of darker skin phenotypes. A review also reported that blood vessels are not visualized in pityriasis rosea lesions in dark skin 5 . This is discordant to studies done in Greece, Turkey, and India where they reported different blood vessel types and patterns since they involved mostly patients of types IV and lighter Fitzpatrick skin types 3,4,9 …”
Section: Discussionmentioning
confidence: 89%
“…Additional characteristics include the presence of globules and blood spots 4 . The characteristic dermoscopic features of pityriasis rosea are collarette of white scales (collarette sign) and yellowish background; however, in dark skin, the background may be brownish‐yellow and the vessels are rarely appreciated 5 . These features vary among patients and in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Bei der seborrhoischen Dermatitis zeigt sich ein ähnliches Bild. Beim Handekzem findet man braunorange Schollen, gelbe Schuppen oder Krusten sowie Punktgefäße [ 3 ].…”
Section: Inflammatorische Erkrankungenunclassified
“…Dieser kann bei der disseminierten, aktinischen, superfiziellen Porokeratose und auch bei Personen mit dunkler Haut hyperpigmentiert sein. Zusätzlich kann man auch kleine randständige dunkelbraune bis schwarze Schollen finden, die histologisch einer Pigmentinkontinenz und Melanophagen in der papillären Dermis entsprechen [ 3 ]. Zusätzlich findet man bei der Porokeratose zentral ein weißes strukturloses Areal und rotbraune Schollen (Abb.…”
Section: Inflammatorische Erkrankungenunclassified
“…Although previous attempts have been done to summarize knowledge on dermoscopic patterns of inflammatory dermatoses in skin of color, no systematic review on this topic does exist [ 1 , 2 ]. Therefore, the International Dermoscopy Society (IDS) Task Force on “Imaging in Skin of Color” promoted the present analysis in order to provide a structured overview on the current state of knowledge about dermoscopy of inflammatory diseases (inflammoscopy) in dark phototypes and align dermoscopic terminology of described findings based on a standardized methodology in order to identify possible gaps and show directions of future studies.…”
Section: Introductionmentioning
confidence: 99%